Clearing Model for Flexibility Dispatching of Virtual Power Plants and Energy Spot Market Considering Transmission-Distribution Coordination - HUANG Fuquan, HE Yujun, GUO Hongye, LI Yun, CHEN Tunan (Dianli jianshe, 2025)
[Objective] The increasing penetration of distributed resources into the distribution grid and their participation in coordinated operations across different levels of the power grid present several challenges. To address these challenges， this study proposes a joint clearing model for virtual power plants （VPPs） participating in local flexibility markets and spot markets. [Methods] Distribution service operators first aggregate the distributed resources into the VPP trading units in distribution network buses. Subsequently， at the distribution network level， a flexibility dispatching model for VPPs on the distribution network is established， which comprehensively considers the constraints of VPPs and the distribution network. Finally， the flexibility dispatching model and spot market-clearing model are co-optimized in a non-iterative manner. To validate the effectiveness of the proposed model， a case study was conducted based on IEEE standard test systems， and a comparative analysis with the market model was performed on the overall cost， transmission-distribution network operation， and clearing efficiency. [Results] Using the proposed method， the expected revenue of the transmission and distribution networks increased by 4.4% in the simulation and computation time reduced by 77.8%， compared with the non-cooperative scenario and iterative calculation method， respectively. [Conclusions] The results demonstrate that the proposed model can meet the flexibility needs of transmission and distribution networks and enhance the integration capacity of the system for renewables.